2004
DOI: 10.1111/j.1349-7006.2004.tb02209.x
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of diet and prostate cancer in Japan: possible protective effect of traditional Japanese diet

Abstract: The age-adjusted incidence of prostate cancer is low in Japan, and it has been suggested that the traditional Japanese diet, which includes many soy products, plays a preventive role against prostate cancer. We performed a case-control study on dietary factors and prostate cancer in order to assess the hypothesis that the traditional Japanese diet reduces the risk of prostate cancer. Four geographical areas (Ibaraki, Fukuoka, Nara, and Hokkaido) of Japan were selected for the survey. Average daily intake of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 70 publications
3
126
2
5
Order By: Relevance
“…We found no association between green-tea consumption and prostate cancer incidence among Japanese men, who consume green tea much more frequently than men in Western countries. Our results conflicted with those of a case -control study in China (Jian et al, 2004), but agreed with those of a prospective study in Hawaii and a casecontrol study in Japan showing no association between green-tea consumption and prostate cancer incidence (Severson et al, 1989;Sonoda et al, 2004).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We found no association between green-tea consumption and prostate cancer incidence among Japanese men, who consume green tea much more frequently than men in Western countries. Our results conflicted with those of a case -control study in China (Jian et al, 2004), but agreed with those of a prospective study in Hawaii and a casecontrol study in Japan showing no association between green-tea consumption and prostate cancer incidence (Severson et al, 1989;Sonoda et al, 2004).…”
Section: Discussionsupporting
confidence: 68%
“…Although laboratory studies have suggested a protective effect of green-tea polyphenols against development of prostate cancer in animal models (Gupta et al, 1999; Saleem et al, 2003), few epidemiological studies have examined the association. A casecontrol study in China found that green-tea intake was associated with a lower risk of prostate cancer (Jian et al, 2004), whereas a prospective study of Japanese Americans in Hawaii and a casecontrol study in Japan found no such association (Severson et al, 1989;Sonoda et al, 2004). The age-standardised incidence of prostate cancer is low in Japan (12.7 per 100 000), being approximately one-tenth of that in the US (Parkin, 2002).…”
mentioning
confidence: 99%
“…[18][19][20] Those studies of the serum equol level revealed two types of men with different metabolic patterns of daidzein to equol; one group is equol producers and the other is equol non-producers whose serum equol was under the detection level (0.5 ng ml À1 ), and the proportion of equol producers among patients with prostate cancer was significantly lower than that among the agematched control group patients. 18 Moreover, the proportion of equol producers was significantly lower among patients with poorly differentiated adenocarcinoma than among those with well or moderately differentiated adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…They recorded all items and amounts of food and drink ingested with the interviewer's assistance. 20 The daily intakes of soybean proteins and isoflavones (total isoflavone, genistein aglycones and daidzein aglycones) during the week before blood sampling were calculated from the above-mentioned data by adding the intake of soybean food items in detail and multiplying the gram-portion size by the soybean foods frequency per day. Calculation of the estimated amount of daily intakes of soybean proteins and isoflavones was carried out by using the published database at the Department of Public Health in Sapporo Medical University.…”
Section: Subjects and Study Designmentioning
confidence: 99%
“…This increased incidence could be partly explained by the widely applied prostate-specific antigen (PSA) screening (Sonoda et al 2004). Needle biopsy is the most common diagnostic modality for prostate cancer after serum PSA screening.…”
Section: Introductionmentioning
confidence: 99%